Managing foreign exchange risks in commercial banks in the Caribbean region - Ramkissoon, Ronald ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Defines the standard risks inherent in foreign reserve management. Looks at the case of Trinidad and Tobago over two different exchange rate regimes. Focuses on the risk management experience of Republic Bank Ltd.